MAQĀSIDIC QUR’ANIC INTERPRETATION AND THE CONTESTATION OF FEMALE CIRCUMCISION IN INDONESIA: BRIDGING TRADITION AND MODERN ETHICS - Mahmudi, Muhammad Aly; Rofiq, Ahmad; Yahya, Imam; Fithrotin, Fithrotin; Ummah, Khurul Aimmatul (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2024)
Female circumcision is a tradition that has been running since Islam existed in Indonesia. The scholars who oblige female circumcision with the tendency of QS. Al Nahl:123 with other verses that show to follow the teachings of Ibrahim (as).  The emergence of this regulation on the ban on circumcision has sparked controversy between state regulations and support by women activists and the WHO on an international scale. This study aims to measure the authority of evidence in the madhab shafiiyah which requires it very urgently from the point of view of the interpretation of maqāṣidī. The research method uses library research by collecting verses and hadiths that are the basis for female circumcision. By looking at the aspects of maqāṣidī using the interpretation approach of maqāṣidī. It is concluded that first: the prohibition of female circumcision is not justified because there is no evidence that leads to haram based on the analysis  of the interpretation of maqashidi, but it is necessary to pay attention if there is a madharat that occurs. Second: The problem of female circumcision is in a way that does not exist in the circumcision law itself so it has many negative effects, so what needs to be regulated is the circumcision procedure with the right medicine, third: Female circumcision is part of Islamic law, so its prohibition causes the elimination of something that has been regulated in Islam.